PHYTOCHEMICAL AND PHARMACOLOGICAL PROFILE OF THE MEDICINAL HERB: BRYOPHYLLUM PINNATUM - A. Latif; K. Ashiq; M. Qayyum; S. Ashiq; E. Ali; I. Anwer (Journal of Animal and Plant Sciences, 2019)
Worldwide, Bryophyllum pinnatum is extensively used to treat the various ailments in folk medicine. The plant is enriched with a diverse range of active therapeutic constituents which are responsible for various significant pharmacological effects. The objective of current study is to highlight the latest evidence-based information regarding pharmacognostical, phytochemical and pharmacological profile of the medicinal plant. Data for the present study was taken from previously published work and to ensure the credibility only indexed research and review articles were used. The databases were included: Scopus, Google Scholar, PubMed, Science Direct, and MEDLINE. Bryophyllum pinnatum contains valuable phytochemicals such as polyphenols, tannins, glycosaponins, flavonoids, steroidal glycosides and many other important chemical constituents that are responsible for its anti-oxidant, anti-pyretic, anti-inflammatory, anti-arthritic, anti-allergic, analgesic, anti-septic, sedative, anti-depression, wound healing, hepatoprotective, nephroprotective, tocolysis, urolithic, anti-psychotic, muscle relaxant, anti-protozoal, anti-microbial and anti-diabetic effects. Bufadienolides have been isolated from the leaves of plant which could be the potential chemotherapeutic agents and hence plant has anti-tumor activity as well. Although, many aspects of the herb have been explored still there is need to carry out a more comprehensive investigation in order to confirm its therapeutic efficacy and to appraise rationale behind its use in folk medicines.
Keywords: Bryophyllum pinnatum; Kalanchoe pinnatum; pharmacognostical; phytochemical; pharmacological; bufadienolides